Resiliensi Permukiman Komunal di Kampung Code Yogyakarta - Nathasya Lintang Ayasha; Kusumaningdyah Nurul Handayani; Maya Andria Nirawati (Universitas Sebelas Maret Surakarta, 2024)
This research aims to discuss the resilience aspect of communal housing and community in kampung kota, Kampung Code Yogyakarta. Community resilience has been part of the solution to mitigate disasters either natural or man-made. Kampung kota is a settlement typology vulnerable to its high density and natural disaster problems. To overcome the risk of high-density and natural disasters mentioned, kampung inhabitant has their way of adapting and resilience. This research tries to discover the way inhabitants cope and adapt to the growing population and buildings between the threats of floods while living on the riverbank of Kali Code. The result shows that the community resilience of Kampung Code inhabitants is reflected in the design of housing, human circulation system, and drainage management in settlement. The findings of this research can be used for future design consideration in the event of revitalization for settlement’s sustainability.